Citrulline production by lactic acid bacteria in Chinese rice wine. Issue 1 (30th January 2018) - Yu, Wei; Li, Xiaomin; Lu, Jian; Xie, Guangfa
Abstract : Ethyl carbamate (EC) is a carcinogenic compound derived from the spontaneous reaction of ethanol with urea or citrulline in Chinese rice wine. Polymerase chain reaction–denaturing gradient gel electrophoresis showed that five species, Lactobacillus fermentum, Lactobacillus plantarum, Lactobacillus brevis, Lactococcus lactis and Lactobacillus coryniformis were the most abundant bacteria in the Chinese rice wine production process. Five strains belonging to these species can degrade arginine primarily in the exponential growth phase and accumulate citrulline in MRS‐Arg medium. In addition, an L. brevis strain was shown to be capable of assimilating citrulline, indicating the potential of this strain suggesting a potential route to reduce citrulline content and ethyl carbamate formation in Chinese rice wine fermentation. Copyright © 2018 The Institute of Brewing & Distilling